Temperature-insensitive pressure transducer based on reflected broadened spectrum with enhanced sensitivity - Vorathin, E.; Hafizi, Z.M.; Aizzuddin, A.M.; Lim, Kok Sing (Elsevier, 2019)
Pasting of half the grating of an FBG sensor on a natural rubber diaphragm was used to sense the pressure measurement. The pressure-induced strain on half of the grating resulted in bandwidth broadening. From the pressure range of 0 kPa to 20 kPa, the pressure sensitivity at 15 dB bandwidth changed was obtained at 77.7 pm/kPa with 99.94% of linearity. Through total reflected power monitoring via photodetector, the pressure transducer retrieved a sensitivity of 0.1686 dB m/kPa and evaded a complex demodulation technique. As a result of the temperature-independent bandwidth change, the pressure transducer was totally temperature insensitive. © 2019 Elsevier B.V.